Becoming and maintainance of sporting form as a criterion of sporting achievement - Зюзь [Zuz Volodymyr] Вoлoдимир Миколайович (Slobozhanskyi Herald of Science and Sport, 2012)
Intercommunication of sporting calendar of competitions, becoming and maintainance of sporting form, dynamics of sporting results in the conditions of small competition cycles is analysed. Address practical experience of the best trainers and professionals and their students, which shows that the higher the qualification of an athlete, the less time it needs to go from a state of high fitness in a state of fitness.